Speech and language therapy service delivery for children with cerebral palsy in the Republic of Ireland : comparative perceptions of parents and speech-language therapists - Janse van Vuren, Marinet (Division of Communication Sciences and Disorders, 2014)
Includes bibliographical references (leaves 213-224).